On the Siegel zeros of quadratic fields and their applications - Razakarinoro, Faratiana Brice (Stellenbosch : Stellenbosch University, 2025)
Razakarinoro, Faratiana Brice. 2024. On the Siegel zeros of quadratic fields and their applications. Unpublished doctoral dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131897